Components of an Obesogenic Environment in Kuwait - Garduño-Diaz, Sara D.; Garduño-Diaz, Philippe Y. (Journal of Nutritional Therapeutics, 2014)
Objective: To analyze the physical, economic, political and sociocultural components of the environment in Kuwait and determine if the country classifies as an obesogenic environment. Design: Observational, cross-sectional study following the ANGELO framework. Data from a popular online food delivery system was accessed and the nutrient composition for these foods was calculated. Setting: Kuwait Results: Meeting the majority of the characteristics required to be identified as such, Kuwait is found to have an obesogenic environment. Availability and accessibility to an almost unlimited amount of food, energy, trans fats and sugars are likely to be significant contributors to obesity and diet-related diseases. Conclusions: In tandem to the diet, harsh climate conditions, sociocultural practices and a lifestyle designed for decreased energy expenditure contribute to the creation of an obesogenic environment.